(untitled) (CIPEEX, 2025)
This summary focuses on rights, more specifically on the importance of the fiduciary sale of real estate for this sector. The study aims to understand the practical application of the institute, the benefits, its historical evolution and the main doctrinal concepts regarding trust. In the topic addressed, there is a need to understand the expansion of the forms of financing that are being made available to rural producers, as a way of promoting Brazilian production and, consequently, fulfilling the social function of rural properties. In this context, the fiduciary sale of real estate in the agrarian sector stands out. The research was prepared with analysis using various research sources, as well as the book “Fiduciary alienation: fiduciary business” by Melhim Namen Chalhub (Rio de Janeiro: Forense, 2020), as well as participation in the National Congress of Agrarian Law, held in Goiânia – Goiás, on 08/23/2024. As a result, it is highlighted that the institute of trust has its origins in Roman Law, in its conception there was the notion of fictitious or provisional sale in which the parties agreed and one of them, called fiduciary, received from another person , fiduciary, ownership over a thing, with an established obligation to return it as soon as a certain purpose was achieved, and the stipulation in an adjective pact was called pactum fiduciae. Inspired by Roman fiducia, based on trust and loyalty, it arrived in Brazil in 1997 with Law 9,514, of November 20, 1997, considered by many scholars as the most well-done law by the Brazilian legislator, as it produces the desired effectiveness in its creation. Professor Wendel de Brito, speaker at the VI National Congress of Agrarian Law, argued that the Fiduciary Alienation of Real Estate tends to be considered a super guarantee or queen of guarantees of the last century. Initially designed for real estate law, it was expanded to other branches of law, such as: banking, industrial and mainly agribusiness. Therefore, it is considered of great importance since it reflects the idea that its guarantee is possible in the business itself, making it possible to acquire a farm by pledging the property itself. It is concluded that some aspects are considered controversial, including being the subject of several discussions in higher courts. It is worth noting: a) there is no consolidated understanding about small rural properties, when given as collateral for fiduciary alienation to the bank and in the event of default, whether or not it is possible to lose the property to pay the debt. In this sense, there are two positions in the Superior Court of Justice admitting unseizability and not admitting it. Those who argue that it is not possible, consider that the Federal Constitution of 1988 (CF/88) does not make sense, protecting small rural properties from mortgages and not protecting them from fiduciary alienation, especially because law 9,514/17 is subsequent to the promulgation of the CF /88.